2000
DOI: 10.1034/j.1600-0714.2000.290801.x
|View full text |Cite
|
Sign up to set email alerts
|

Disorder‐specific changes in innervation in oral lichen planus and lichenoid reactions

Abstract: The peripheral nervous system was analysed in the oral mucosa of eight patients with oral lichen planus (OLP), five with a lichenoid reaction (LR) and three with mild chronic inflammation (MCI), by morphometric analysis of nerve fibres containing immunoreactive PGP 9.5, substance P (SP), calcitonin gene-related peptide (CGRP), vasoactive intestinal polypeptide (VIP), or C-flanking peptide of neuropeptide Y (CPON). Overall nerve fibre density was higher in OLP (P=0.039) and LR (P=0.026) compared with healthy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…Although numerous papers evidenced that neurogenic inflammation contributes to the pathogenesis of various inflammatory diseases such as Sjögren's syndrome, psoriasis, dermatitis, arthritis and asthma, only few reports mentioned possible neurogenic factors associated with OLP [1] . Pro-inflammatory neuropeptides, mainly substance P and calcitonin gene-related peptide, were thought to be released from sensory nerve endings via activation of neuronal TRPV1 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous papers evidenced that neurogenic inflammation contributes to the pathogenesis of various inflammatory diseases such as Sjögren's syndrome, psoriasis, dermatitis, arthritis and asthma, only few reports mentioned possible neurogenic factors associated with OLP [1] . Pro-inflammatory neuropeptides, mainly substance P and calcitonin gene-related peptide, were thought to be released from sensory nerve endings via activation of neuronal TRPV1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Different clinical manifestations exist, such as reticular, papular, athrophic and erosive lichen. Most frequently, it occurs bilaterally on the buccal mucosa [1] . Histologically, OLP is characterized by band-like subepithelial lymphocytic infiltration in the connective tissue, ortho-and parakeratosis and increased spinous cell layer (acanthosis) in the epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…[81] Upon induction by ultraviolet rays, T regulatory cells tend to migrate to local lymph nodes and thus may not inhibit the elicitation of cutaneous immune reactions. [82] Although changes in cutaneous nerves are of relatively less importance in the pathogenesis of lichen planus, Nissalo et al .,[83] showed an increase in nerve fiber density in oral lichen planus and lichenoid reactions compared to healthy mucosa which was compatible with sprouting and collateral formation (neural component). [83] The primary pathology in lichen planus is immune dysregulation as seen by increase in population of dermal CD4+ and CD8+ T cells with infiltration of epidermis with CD8+ T cells culminating in keratinocyte necrosis.…”
Section: Pathogenesis Of Isotopic Responsementioning
confidence: 99%
“…[82] Although changes in cutaneous nerves are of relatively less importance in the pathogenesis of lichen planus, Nissalo et al .,[83] showed an increase in nerve fiber density in oral lichen planus and lichenoid reactions compared to healthy mucosa which was compatible with sprouting and collateral formation (neural component). [83] The primary pathology in lichen planus is immune dysregulation as seen by increase in population of dermal CD4+ and CD8+ T cells with infiltration of epidermis with CD8+ T cells culminating in keratinocyte necrosis. The effect of ionizing radiation in the induction of lichen planus like lesions is not proven conclusively (as psoralen plus ultraviolet therapy has been used to treat lichen planus), but it is not unreasonable to assume that immunologic and neural changes that result in the aftermath of radiation damage may together lead to immune dysfunction and hence lichen planus.…”
Section: Pathogenesis Of Isotopic Responsementioning
confidence: 99%
“…All of these alterations might be the consequence of chronic inflammation as well as changes in innervation. Nissalo et al . (2000 ) have reported that overall nerve density was higher in oral lichen planus compared with healthy oral mucosa where the nerve fibres have sprouting and collateral formation.…”
Section: Introductionmentioning
confidence: 99%